2018
DOI: 10.4103/jrms.jrms_1191_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermented camel milk on glucose metabolism, insulin resistance, and inflammatory biomarkers of adolescents with metabolic syndrome: A double-blind, randomized, crossover trial

Abstract: Background:This study, for the first time, aimed to assess the effects of fermented camel milk (FCM) on glycemic and inflammatory parameters related to metabolic syndrome (MetS), an aggregation of cardiometabolic risk factors, in adolescents.Materials and Methods:In a double-blind, randomized crossover trial, overweight/obese adolescents (fulfilling MetS criteria, aged 11–18 years) were randomly assigned to receive FCM 250 cc per day for an 8-week period, a 4-week washout, and then diluted cow's yogurt (DCY) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…The study participants were consecutively recruited from March 2016 to December 2016 through screening the overweight or obese adolescents referring to the affiliated clinic of Child and Growth Development Research Center (in Amin Hospital, IUMS), and the private practice offices of the study's principal investigators. More details about the methods and procedures of the main study have been presented elsewhere (18,19).…”
Section: Study Design and Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study participants were consecutively recruited from March 2016 to December 2016 through screening the overweight or obese adolescents referring to the affiliated clinic of Child and Growth Development Research Center (in Amin Hospital, IUMS), and the private practice offices of the study's principal investigators. More details about the methods and procedures of the main study have been presented elsewhere (18,19).…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…Lactobacilli were used in the production of FCM as well. Dietary constituents of them are presented elsewhere (18)(19).…”
Section: 2 Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Camel doogh is the homemade fermented camel milk made by Turkmens in Iran. [ 12 ] Our previous study showed that most of the Lactobacillus species isolated from camel dough have the potential of antimicrobial and antioxidant activities. [ 13 ] The aim of the present study is to investigate the anticancer activity of these Lactobacillus strains and separate a bioactive fraction from their extracellular methanol extracts by thin layer chromatography (TLC) and evaluate the apoptotic effect of the fraction against cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic potential of camel milk is being proclaimed by numerous reports with diabetes treatment being one of popularly studied aspect. [234] We herewith aim to critically evaluate current evidences assessing the use of camel milk for the reduction of diabetes risk and if so which type of diabetes.…”
Section: Introductionmentioning
confidence: 99%